The effect of uniaxial stress to spin reorientation transition in magnetic thin-films: Monte Carlo investigation - Y. Laosiritaworn (2018)
In this work, we studied magnetic thin-films with thicknesses ranging from 2 to 4 layers via Monte Carlo simulations. The magnetic systems were modelled using anisotropic classical Heisenberg spins under the influence of mechanical uniaxial stresses. The study was performed with a spin-flip algorithm to investigate how the averaged magnetic properties, including their microscopic orientation, depend on temperatures, thicknesses and the magnitude of the mechanical uniaxial stress. From our results, it is found that the applied stress reduces the spin reorientation temperatures (from the out-of-plane to the in-plane direction) in a same way as increasing the number of thicknesses. The observations are in good agreement with related experiments. © 2005 Elsevier B.V. All rights reserved.